Cheese and Yogurt By-Products as Valuable Ingredients for the Production of Prebiotic Oligosaccharides - Athanasios Limnaios; Maria Tsevdou; Eirini Zafeiri; Evangelos Topakas; Petros Taoukis (Dairy, 2024)
The growing global market of dairy products has led to the need for alternative approaches regarding whey valorization, which is the primary by-product of cheese and strained yogurt production. In this context, prebiotic galactooligosaccharides can be produced enzymatically from whey using commercially available β-galactosidases. A comparative study was conducted to assess the production of galactooligosaccharides from sweet and acid whey, thereby employing two commercial β-galactosidases from Aspergillus oryzae and Kluyveromyces lactis. The study considered the initial lactose content and enzyme load as variables. The maximum yields of galactooligosaccharides in concentrated sweet whey (15% w/v initial lactose) and raw acid whey (3.1% w/v initial lactose) reached 34.4 and 14.7% with lactase from Kluyveromyces lactis (0.13 U/mL), respectively. The corresponding galactooligosaccharide yields for lactase from Aspergillus oryzae were equal to 27.4 and 24.8% in the most concentrated sweet and acid whey, respectively, using enzyme loads of 2 U/mL in sweet whey and 1 U/mL in acid whey. Concerning the profile of the produced galactooligosaccharides, the Kluyveromyces lactis lactase hydrolyzed lactose more rapidly and resulted in higher levels of allolactose and lower levels of 6-galactosyl-lactose, compared to the lactase from Aspergillus oryzae, and achieved in both cases a polymerization degree of up to six.